The Digital-Based Innovative Learning of Music Subject to Cultivate The Character Values of Students During Covid-19 Pandemic - Dewannata, Danial Aghnia; Suharto, Suharto; Syarif, Muh. Ibnan (Universitas Negeri Semarang, 2021)
The condition of Covid-19 pandemic in the educational sector has made the learning activities cannot be conducted face-to-face as usual and the educational institutions such schools are closed in accordance with the government regulation. However, the learning condition cannot stop although the schools are closed temporarily. Teachers need to adapt with the condition and implement the innovation based on the digital development by utilizing various digital devices that can be used for the learning activity to cultivate the character values to the students. This research aims to describe and analyze the teacher’s innovation in the digital-based innovative learning during the music subject with the purpose of cultivating the students’ character values in SMA Negeri 1 Bumiayu during the Covid-19 pandemic. This research used qualitative method with the educational anthropology, musicology, and technology & communication approach. The process of data collection is conducted through observation, interviews, and literature study. The data analysis is conducted through three activities by Miles and Huberman, namely data reduction, data display, and conclusion. The results of the research show that the digital-based innovative learning model of music subject can be used to cultivate the character value of the students through the digital devices which are used during the online learning activity of music subject both theoretically and practically in the form of appreciation and creative activities. The material taught is innovated through the help of digital devices as the stimulus to raise the students’ awareness as well as cultivate the character values which will give positive impact on the success of the character values.